ANTARA PRIVASI DAN ILMU PENGETAHUAN: KAJIAN ATAS PENGECUALIAN HAK SUBJEK DATA PRIBADI PADA PENELITIAN ILMIAH - Muhammad Anshori; Shofi Munawwir Effendi (Veritas et Justitia, 2026)
The transformation of education and sustainable development across sectors increasingly depends on scientific research as a foundation for evidence-based policymaking, regulatory development, and human capital advancement. At the same time, the use of personal data in research activities raises concerns regarding the protection of the constitutional right to personal data and privacy guaranteed under Article 28C paragraph (1) of the 1945 Constitution of Indonesia. Although Article 15 paragraph (1) letter e of Law Number 27 of 2022 on Personal Data Protection exempts certain rights of personal data subjects for scientific research purposes, the Law does not provide sufficient legal certainty regarding the mechanisms and safeguards governing such exemptions. This study examines the adequacy of Indonesia’s legal framework on personal data protection in scientific research and formulates recommendations for strengthening regulatory safeguards. Employing a statutory approach and comparative analysis, the research compares Indonesian regulations with legal and ethical safeguards applied in the United States concerning research involving personal data. The research finds that the exemption of data subject rights for scientific research must be accompanied by clear legal standards, institutional oversight, and ethical safeguards to prevent misuse of personal data. It recommends the establishment of comprehensive governance mechanisms involving government institutions, higher education institutions, and researchers to ensure that scientific advancement remains consistent with personal data protection principles.